Replication of Simian Virus 40 Deoxyribonucleic Acid: Analysis of the One-Step Growth Cycle - Manteuil, Simone (1973)
The time course of replication of simian virus 40 deoxyribonucleic acid (DNA) was investigated in growing monolayer cultures of subcloned CV1 cells. At multiplicities of infection of 30 to 60 plaque-forming units (PFU)/cell, first progeny DNA molecules (component 1) were detected by 10 hr after infection. During the following 10 to 12 hr, accumulation of virus DNA proceeded at ever increasing rates, albeit in a non-exponential fashion. The rate of synthesis then remained constant, until approximately the 40th hour postinfection, when DNA replication stopped. Under these conditions, the duration of the virus growth cycle was approximately 50 hr. The time needed for the synthesis of one DNA molecule was found to be approximately 15 min. At multiplicities of infection of 1 or less than 1 PFU/cell, the onset of the linear phase of DNA accumulation was delayed, but the final rate of DNA synthesis was the same, independent of the input multiplicity. This was taken as a proof that templates for the synthesis of viral DNA multiply in the cell during the early phase of replication. However, the probability for every replicated DNA molecule to become in turn replicative decreased constantly during that phase. This could be accounted for by assuming a limited number of replication sites in the infected cell.